Menakar Digital Customer Service Machine Menggunakan Human Organization Technology Model - Nidiacitra, Luh; Gede Sri Darma (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
This study aims to analyze the factors that influence BNI customers in using digital service machines, namely Digi CS or Digital Customer Service Machine Using the Human Organization Technology (HOT-FIT) Model. This research is a descriptive-quantitative research with 134 respondents as who are customers of BNI Renon Branch using accidental sampling. Data was obtained through an open questionnaire points to measure or obtain opinions or responses from customers regarding the eight variables in this research, namely System Quality, Information Quality, Service Quality, System Use, User Satisfaction, Organization Structure, Environment and Net Benefits. The research results show that technological factors, namely the variables Information Quality, Service Quality, System Quality, have an influence on human factors, namely System Use, User Satisfaction, where these human factors also influence Net Benefits. Apart from that, organizational factors, namely Structure, influence the net Benefit but not the Environment which does not influence the Net Benefit.